Penerapan Pemberian Tugas Proyek Terhadap Hasil Belajar IPA Pada Peserta Didik Pulau Barrang Lompo - Syamsuddin, Afdhal Fatawuri; Rahman, Hardianto; Faisal, Muhammad (Universitas Islam Ahmad dahlan, 2024)
This research focuses on the condition of education in Makassar, especially in island areas such as Barrang Lompo, where educational facilities and resources are still limited. The aim is to evaluate the effectiveness of Project-Based Learning (PjBL) on improving science learning outcomes of grade 10 students at Barrang Lompo High School. This pre-experimental study used a One-Shot Case Study Design with two main variables: project assignment and science learning outcomes. The subjects were 28 grade 10 students, with data collected through cognitive tests and observation sheets measuring psychomotor skills. Data were analyzed descriptively, by presenting statistics such as mean scores and frequency distributions. The results showed that the implementation of PjBL had a positive impact on cognitive and psychomotor learning outcomes. The cognitive assessment showed that 75% of students met the minimum completion criteria (KKM), while the psychomotor assessment showed that 100% of students reached the standard. The results concluded that PjBL can significantly improve educational outcomes in under-resourced areas by encouraging critical thinking, problem-solving skills and active student engagement. Future research is recommended to further explore and validate these findings across different subjects and contexts